Cultural Self-Efficacy of Second-Degree Nursing Students in Providing Care to Immigrants. - Miskin, Predrag; Matthews, Eric; Wallace, Lisa A.; Fox, Sylvia (Journal of Cultural Diversity)
The purpose of this study was to determine the levels of perceived cultural self-efficacy of senior students in second-degree pre-licensure nursing programs in the provision of culturally appropriate care to immigrants. The study employed a quantitative, non-experimental design with survey methodology. The convenience sample consisted of 117 senior students enrolled in accelerated bachelor of sciences in nursing and entry levels master of sciences programs. The study used Bernal and Froman's Cultural Self-Efficacy Scale (CSES). The study found that the participants had low levels of transcultural self-efficacy. There was no association between the participants'demographic characteristics and their CSES scores. These findings were consistent with the findings of previous studies that surveyed traditional nursing students. The study provided important assessment data on learning needs of second-degree nursing student concerning the provision of culturally congruent care.